Microwave-assisted extractions of active ingredients from plants - Chan, C.H.; Yusoff, R.; Ngoh, G.C.; Kung, F.W. (Journal of Chromatography A, 2011)
Microwave-assisted extraction (MAE) is widely employed in the analysis and the extraction of active compounds from plants. This review summarizes the research done during the last decade on the MAE of active ingredients from plants. Advances and modifications to improve the performance of MAE are presented and discussed in detail. Modified MAE such as vacuum microwave-assisted extraction (VMAE), nitrogen-protected microwave-assisted extraction (NPMAE), ultrasonic microwave-assisted extraction (UMAE), dynamic microwave-assisted extraction (DMAE) and other advancements in MAE are also detailed in this article. In addition, the microwave extraction procedures and the important parameters influencing its performance are also included, together with the advantages and the drawbacks of each MAE techniques.